Using AHP and ANP in Public Administration - Raykowski, Andrew (Univerzita Pardubice, 2021)
An overview of multiple-criteria decision-making systems, focusing on the Analytic Hierarchy Process and Analytic Network Process, is provided. An algorithm for applying these methods to a case study of the euro convergence criteria (Maastricht criteria), with eurozone candidate countries compared as alternatives, is then developed. Testing the algorithm on historical data produces several results showing close parallels to actual country join dates.
Využití AHP a ANP ve veřejné správě
Keywords: MCDM; AHP; ANP; euro; convergence criteria; Maastricht criteria; MCDM; AHP; ANP; euro; konvergenční kritéria; maastrichtská kritéria